Anti‐Müllerian hormone measurement for the diagnosis of polycystic ovary syndrome. (7th December 2017) - Sathyapalan, Thozhukat; Al‐Qaissi, Ahmed; Kilpatrick, Eric S.; Dargham, Soha R.; Atkin, Stephen L.
Summary: Objective: Anti‐Müllerian hormone (AMH) is derived from the small antral follicles, and an elevated level has been suggested to add value to the Rotterdam criteria for the diagnosis of PCOS in cases of diagnostic uncertainty. Therefore, the role of AMH in the classical phenotype of PCOS was defined within a Caucasian population. Design: This was a cross‐sectional study. Patients: Sixty Five women without PCOS and 110 women with PCOS fulfilling all 3 diagnostic Rotterdam criteria. Measurements: The main outcomes were the utility of serum AMH for the diagnosis of PCOS and its relationship to the metabolic parameters. Results: Anti‐Müllerian hormone was increased in PCOS compared to controls ( P  < .001). Areas under the receiver operator curve showed AMH to be predictive of PCOS (0.76) using a cut‐off AMH of 46 pmol/L, which is derived from the 95 th percentile of the controls that gave a 41% sensitivity and 86% specificity; an AMH cut‐off of 35 pmol/L gave a 55% sensitivity and 79% specificity. Age‐ and BMI‐adjusted multiple logistic regression showed that AMH was more predictive of PCOS independently of either serum testosterone (T) (OR = 4.04; 95% CI 1.42‐11.11; P  = .007) or free androgen index (FAI) (OR = 3.90; 95% CI 1.40‐10.83; P  = .009). Conclusion: Whilst an elevated AMH has poor sensitivity, it is fourfold more likely to be associated with a diagnosis of PCOS, and supplementary to biochemical parameters will make a positive diagnosis of PCOS in 22% of patients when neither serum testosterone nor FAI is elevated.